Sexual conflict and the maintenance of genetic variation in natural populations. Issue 18 (15th September 2018) - Meisel, Richard P.
Abstract: Understanding the factors that maintain genetic variation in natural populations is a foundational goal of evolutionary biology. To this end, population geneticists have developed a variety of models that can produce stable polymorphisms. In one of the earliest models, Owen (1953 ) demonstrated that differences in selection pressures acting on males and females could maintain multiple alleles of a gene at a stable equilibrium. If the selection pressures act in opposite directions in males and females, we refer to this as (inter‐) sexual conflict or sexual antagonism (Arnqvist & Rowe, 2005 ). Testing if sexual conflict maintains genetic variation in natural populations is a tremendous challenge—it requires both identifying loci that harbor sexually antagonistic alleles and determining whether those alleles are maintained as stable polymorphisms (Mank, 2017 ). Doing so genome‐wide is even harder because it is not tractable to identify sexually antagonistic alleles and test for stable polymorphisms at all loci. Dutoit et al. (2018 ) confront this challenge in a paper published in this issue of Molecular Ecology . Using gene expression and population genomic data from the collared flycatcher, Dutoit et al. (2018 ) identify associations and correlations between genomic signatures of balanced polymorphisms and sexual conflict.